(untitled) (Bangladesh Journal of Agricultural Research, 2022)
The field experiment on broccoli (Brassica oleracea var. italica L.) taking three planting dates viz., 21 November, 01 December and 11 December, 2019 and four genotypes, namely BARI Broccoli-1, Thiland-1, Thailand-2 and Japan-1 was conducted during rabi season of 2019-20 in the experimental field of Bangladesh Agricultural Research Institute, On-Farm Research Division, Dawlatpur, Khulna to investigate the effect of planting dates on the growth and yield of broccoli genotypes on saline soil having salinity level 2.6-4.8 dS/m . The experiment was laid out in 4 x 3 factorial randomized complete block design with three replications. The genotype Japan-1 gave maximum number of leaves/plant (25.44), fresh weight of leaves/plant (830.77 g), fresh weight of stem/plant (311.69 g), fresh weight of root/plant (53.47 g), which were not reflected into yield and yield attributes. The genotype Thailand-2 produced significantly lower all growth characters than those of Japan-1 but gave the highest curd diameter (18.11 cm, curd weight (360.19 g) and curd yield (16.01 t/ha) of all genotypes. Broccoli planted on 21 November initiated early flower head, recorded maximum number of leaves/plant (27.84), fresh weight of leaves/plant (800.87 g), fresh weight of stem/plant (313.73 g), fresh weight of root/plant (60.79 g), curd diameter (17.01 cm), curd weight (285.65 g) and curd yield (12.69 t/ha). The genotype Thiland-2 coupled with 21 November showed the best performance in respect of curd weight (419.74 g/plant) and curd yield (18.66 t/ha). Bangladesh J. Agril. Res. 45(4): 419-429, December 2020